Tingkat Efektivitas Penggunaan Flocullant Jenis Clarifloc untuk Menurunkan Nilai TSS (Total Suspended Solid) pada Settling Fond Bantian-54 PT Indo Muro Kencana Provinsi Kalimantan Tengah - L., Prayoga Betrio; Usup, Hepryandi Luwyk Djanas; Novalisae; Noveriady; Putrawiyanta, I Putu (Universitas Pahlawan Tuanku Tambusai, 2024)
Indo Muro Kencana is a company that operates in the field of gold and silver mining using the Open Pit method. This mining activity increases water turbidity due to high Total Suspended Solids (TSS). The method used in this research is quantitative and descriptive methods. The results showed that the use of Clarifloc flocculant significantly reduced TSS values, with varying effectiveness in each settling pond compartment and per hour. In accordance with the results of laboratory research, it shows that the reduction in TSS in the Bantian 5-4 settling pond of PT Indo Muro Kencana has been efficient with the test value for each compartment getting an average TSS value at the inlet = 8,136.4 mg/l down in pond 1 = 402.9 mg /l, pool 2 = 239.7 mg/l, pool 3 = 34.8 and outlet = 16.7 mg/l. The water output in pool 3 and the outlet has entered the quality standard, while in the hourly experiment the decrease in TSS is <2 hours, it has entered the quality standard. The length of settling time depends on the amount of discharge entering the settling pond with real data in the field of pump discharge of 0.16 m3/s, the length of settling time. 32.3 hours. Based on table 5, TSS data from the Bantian 5-4 settling pond hourly experiment, the reduction in TSS was very effective because the average TSS value decreased by 46.33% after being given flocculant in the hourly experiment, which was <3 hours. The TSS value was already below 200 mg/l. The quality standards that have been set are in accordance with the quality standards that refer to Minister of Environment Decree No. 202 of 2004 concerning: Waste water quality standards for gold and/or copper ore mining businesses and/or activities namely TSS mg/l 200, SNI 06-6989-3-2004.